Impact of Access Cavity Design on Fracture Resistance of Endodontically Treated Molars: A Systematic Review - Saeed M; Al-Obadi M; Salim A; Alsawaf AY; Hadi K (Dove Medical Press, 2021)
Musab Saeed,1 Mona Al-Obadi,2 Asma Salim,2 Alaa Y Alsawaf,2 Karrar Hadi3 1Department of Clinical Sciences, Ajman University, Ajman, United Arab Emirates; 2Ajman University, Ajman, United Arab Emirates; 3College of Dentistry, Ajman University, Ajman, United Arab EmiratesCorrespondence: Musab SaeedDepartment of Clinical Sciences, Ajman University, Ajman, United Arab EmiratesTel +97167056211Email m.saeed@ajman.ac.aeObjective: The main aim of this present systematic review is to ascertain whether a conservative endodontic cavity (ConsAC) has a better fracture resistance than a traditional access cavity (TradAC) in endodontically treated molars.Materials and Methods: Three independent reviewers researched without limits in multiple engines: PubMed, ScienceDirect, Scopus, ResearchGate, EBSCOhost, Wiley Online Library, and Google Scholar, in addition to reference and hand search. Articles were chosen according to a certain inclusion and exclusion criteria, which, in brief, are in vitro studies assessing the fracture resistance difference between ConsAC and TradAC performed on extracted sound human molar teeth. A quality assessment criteria was produced to evaluate the chosen articles and categorized them according to their risk of bias into low, moderate and high.Results: Out of a total of 105 studies, which were obtained from seven different search engines, only eight in vitro studies were included after eliminating the duplicates followed by the application of the eligibility criteria. Five of the articles showed low risk of bias while the others revealed a moderate risk of bias.Conclusion: To sum up, there is insufficient evidence to give a final decision whether ConsAC is more advantageous than TradAC in terms of fracture resistance and further studies regarding this topic are needed.Keywords: traditional access cavity, conservative access cavity, endodontically treated teeth, molars, fracture resistance